IMPLEMENTASI PEMENUHAN HAK PENDIDIKAN ANAK BINAAN DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS I BLITAR - Anami, Salmaa Sekar; Simanjuntak, Meitisa Vanya (Politeknik Ilmu Pemasyarakatan, 2025)
The fulfillment of educational rights for children in the Special Child Development Institution (LPKA) is crucial to ensure their future success despite legal conflicts. This research, focusing on the implementation of educational rights for juvenile inmates at LPKA Class I Blitar, explores the policies, curriculum, facilities, and obstacles in the process. Conducted using a qualitative explanatory method, the research includes observations and interviews with six informants, including three juvenile inmates, two LPKA staff members, and one teacher. The results reveal that, although the LPKA provides formal education (elementary to high school levels), it faces challenges such as limited resources, inadequate facilities, and the lack of motivation among juvenile inmates. Additionally, the short duration of sentences further complicates continuous education. LPKA collaborates with educational institutions, but budget constraints, incomplete administrative requirements, and inadequate teaching staff hinder optimal learning outcomes. Recommendations include better budget planning, more support for incomplete documentation, and motivational programs for both educators and students to enhance learning participation and success.